2019
DOI: 10.4103/jispcd.jispcd_258_18
|View full text |Cite
|
Sign up to set email alerts
|

The impact of background music in reducing stress during preclinical dental laboratories

Abstract: Objective: The reported high level of stress among dental students and its consequences, considering the known benefits of background music (BM). This study was designed to evaluate students’ level of stress and impact of BM on their efficiency of work, performance, and learning ability during preclinical laboratory. Materials and Methods: In this cross-sectional questionnaire study, 61 preclinical students from the College of Dentistry, Ajman university-Fujairah campus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It has been shown that music therapy has a positive effect on patients' emotional states during dental treatments and also reduces the stress levels of clinicians during demanding procedures or busy schedules as well as undergraduate dental students who perform preclinical training [15,32,33]. Similar to the present ndings of this study, Felszeghy et al [21] also showed that the music reduced stress but also increased motivation of the dental students to learn and practice in preclinical cariology training.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It has been shown that music therapy has a positive effect on patients' emotional states during dental treatments and also reduces the stress levels of clinicians during demanding procedures or busy schedules as well as undergraduate dental students who perform preclinical training [15,32,33]. Similar to the present ndings of this study, Felszeghy et al [21] also showed that the music reduced stress but also increased motivation of the dental students to learn and practice in preclinical cariology training.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, Varma et al [15] indicated a strong positive relation between stress and background music in the preclinical laboratory. In these two studies, various types of music were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was not statistically significant. This is supported by a study done on Iranian dental students, which showed that BM can reduce the anxiety and depression of dental students [20,22]. Multiple reports on using BM claim that it alters mood, shifts temporal orientation, triggers physiological changes, minimizes anxiety, calms the mind, lowers distraction, enhances focus, and supports performance [23][24][25].…”
Section: Discussionmentioning
confidence: 74%